How Residence Permits Affect the Labor Market Attachment of Foreign Workers: Evidence from a Migration Lottery in Liechtenstein - Berno Buechel; Selina Gangl; Martin Huber (Center for Economic Studies and ifo Institute (CESifo), 2021)
We analyze the impact of obtaining a residence permit on foreign workers' labor market and residential attachment. To overcome the usually severe selection issues, we exploit a unique migration lottery that randomly assigns access to residence permits for workers with an employment contract in Liechtenstein, which is situated centrally in Europe. Using an instrumental variable approach, our results show that lottery compliers raise their employment probability in Liechtenstein by on average 24 percentage points across outcome periods (2008 to 2018) as a result of receiving a permit. Relatedly, their activity level and employment duration in Liechtenstein increase by on average 20 percentage points and 1.15 years, respectively, over the outcome window. These substantial and statistically significant effects are predominantly driven by individuals not (yet) working in Liechtenstein prior to the lottery rather than by previous cross-border commuters, but even for the latter group, positive employment effects emerge in the longer run. Indeed, we find both the labor market and residential effects to be persistent even several years after the lottery with no sign of fading out. These results suggest that granting resident permits to foreign workers can be effective to foster labor supply, despite the alternative of commuting cross-border from adjacent regions.
Keywords: F22; J61; 330; international migration; cross-border commuting; natural experiment; lottery